Pengalaman Perawat dalam Memberikan Asuhan Keperawatan pada Pasien Readmission - Santi, Kartika; Purba, Jenny Marlindawani; Nasution, Siti Zahara (Journal of Telenursing (JOTING), 2024)
This study aims to explore the experiences of nurses in providing nursing care to patients undergoing readmission at the Prof. Mental Hospital. Dr. Muhammad Ildrem Medan. This type of research is qualitative with a descriptive phenomenological approach. The research results showed that there were 5 themes, namely: 1) Care is given to readmission patients, 2) Nurses' feelings about caring for readmission patients, 3) Identifying the causes of readmission patients, 4) Prevention strategies for readmission patients, 5) Barriers to caring for readmission patients. Conclusion, To prevent readmissions, nurses are required to be able to provide education about illnesses and how to care for family members with mental disorders, train families as supervisors of taking medication, and strategies for overcoming crises when caring for people with mental disorders at home. Keywords: Nursing Care, Nurse Experience, Readmission.